Teaching online : a practical guide - Ko, Susan, ....-; Rossen, Steve, ....- (New York : Routledge, 2017)
Teaching Online: A Practical Guide is an accessible, introductory, and comprehensive guide for anyone who teaches online. The fourth edition of this bestselling resource has been fully revised, maintains its reader-friendly tone, and offers exceptional practical advice, new teaching examples, faculty interviews, and an updated resource section. New to this edition: entire new chapter on MOOCs (massive open online courses); expanded information on teaching with mobile devices, using open educational resources, and learning analytics; additional interviews with faculty, case studies, and examples; spotlight on new tools and categories of tools, especially multimedia. Focusing on the "hows" and "whys" of implementation rather than theory, the fourth edition of Teaching Online is a must-have resource for anyone teaching online or thinking about teaching online.